2016
DOI: 10.21475/ajcs.2016.10.12.p7444
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and control of root knot nematode in crops: A review

Abstract: Root-knot nematode (RKN) which comes from Meloidogyne species is an obligate, parasitic nematode which can be found in varieties of plants, considered as a host to that particular nematode. Their potential host range encompasses more than 3000 plant species. The presence of RKN in the crops becomes one of the major problems nowadays because they cause great agriculture loss. Among the many genera of nematodes having some economic impact, Meloidogyne spp. are responsible for a large part of the annual 100 billi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 8 publications
0
56
0
1
Order By: Relevance
“…The studies concluded that these nematodes can infect more than 3000 host plant species in agriculture (Jung and Wyss, 1999;Hussey and Janssen, 2002;Abad et al, 2003. Consequentially, among the many nematodes, the groups having some economic impact, Meloidogyne spp., are responsible for a large part of the annual 100 billion dollar losses attributed to nematode damage worldwide (Ralmi et al, 2016). The yield losses in vegetables such as tomato, melon, and eggplants exceed 30% (Sikora and Fernández, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The studies concluded that these nematodes can infect more than 3000 host plant species in agriculture (Jung and Wyss, 1999;Hussey and Janssen, 2002;Abad et al, 2003. Consequentially, among the many nematodes, the groups having some economic impact, Meloidogyne spp., are responsible for a large part of the annual 100 billion dollar losses attributed to nematode damage worldwide (Ralmi et al, 2016). The yield losses in vegetables such as tomato, melon, and eggplants exceed 30% (Sikora and Fernández, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…), among the most destructive agricultural pests, are responsible for a large portion of the considerable economic losses, estimated at about $77 billion a year caused by phytopathogenic nematodes worldwide (Ralmi et al, 2016; Yadav, 2017). Of the more than 100 Meloidogyne species, M. incognita , M. hapla , M. javanica , and M. arenaria are considered the most widespread and economically important plant-parasitic RKNs (Elling, 2013; Jones et al, 2013; Molinari, 2009).…”
mentioning
confidence: 99%
“…Root-knot nematodes (Meloidogyne spp.) are the most economically damaging group of plant-parasitic nematodes (PPNs) worldwide [102][103][104]. The genus Meloidogyne is composed of approximately 100 species and parasitizes thousands of plant species [105,106].…”
Section: Effect Of Biogas Digestate Application On Root-knot Nematodementioning
confidence: 99%